Optimal Torque Control Performance of DTC of 5-Phase Induction Machine - Lourdes Victor Raj, Logan Raj; Jidin , Auzani; Ibrahim, Zulkifli; Abdul Karim, Kasrul; Said, Mohamed Azmi; JOPRI, MOHD HATTA (2013)
In this paper, optimal voltage vector selection for high-performance of Direct Torque Control (DTC) of five-phase induction machine is presented. The de-coupled control of stator flux and electromagnetic torque based on hysteresis controllers as employed in conventional DTC is applied to retain the simplicity and to provide quick instantaneous control. A single complete look-up table that selects the most optimal voltage vectors according to the motor operating condition is proposed. This improves DTC performances such as excellent torque dynamic control, minimization of torque ripple, high-efficiency (due to lower switching frequency) and extension of constant torque region. All the improvements are validated through simulation results.